The Study of Interruption in a Mixed-Gender Talk Show Conversation - Ririn Rubiyanti (Passage, 2017)
The phenomenon of interruption in a speech event has attracted the attention of many researchers. This study investigates the phenomenon in the context of a talk show in an Indonesian TV show. It is an attempt to answer: 1) the types of interruption occur in the talk show; 2) the functions of interruption; 3) politeness strategies that are used by the speakers when interrupting; and 4) the possible factors that affect speakers to interrupt. The data were taken from an Indonesian talk show entitled “Ini Talk Show”. The duration of the talk show is 14 minutes. This research mainly uses qualitative method in collecting and analyzing the data. However, a simple quantitative measure in the form of categorical measurement is also used to count the frequency of occurrence of particular data. The types and functions of interruption were analyzed using Ferguson (1977) theory and French Local (1983) theory. Moreover, politeness strategies that are used by the speakers were analyzed using Brown Levinson (1987) theory. Lastly, the possible factors that affect speakers to interrupt were analyzed following Wardhaugh (1985). The study found that most of the interruptions are initiated by female speakers. In mitigating to avoid the hearer’s face, the interrupters mostly use positive politeness strategies. Lastly, the interrupters interrupt because of many factors; mostly the interrupters interrupting to break up the conversation. Keywords: Interruption, politeness, and gender